Cholecystokinin system is involved in the anorexigenic effect of peripherally applied palmitoylated prolactin-releasing peptide in fasted mice - Pirník, Z; Kořínková, L; Osacká, J; Železná, B; Kuneš, J; Maletínská, L (Physiological research, 2021)
Prolactin-releasing peptide (PrRP) has been proposed to mediate the central satiating effects of cholecystokinin (CCK) through the vagal CCK1 receptor. PrRP acts as an endogenous ligand of G protein-coupled receptor 10 (GPR10), which is expressed at the highest levels in brain areas related to food intake regulation, e.g., the paraventricular hypothalamic nucleus (PVN) and nucleus of the solitary tract (NTS). The NTS and PVN are also significantly activated after peripheral CCK administration. The aim of this study was to determine whether the endogenous PrRP neuronal system in the brain is involved in the central anorexigenic effect of the peripherally administered CCK agonist JMV236 or the CCK1 antagonist devazepide and whether the CCK system is involved in the central anorexigenic effect of the peripherally applied lipidized PrRP analog palm-PrRP31 in fasted lean mice. The effect of devazepide and JMV236 on the anorexigenic effects of palm-PrRP31 as well as devazepide combined with JMV236 and palm-PrRP31 on food intake and Fos cell activation in the PVN and caudal NTS was examined. Our results suggest that the anorexigenic effect of JMV236 is accompanied by activation of PrRP neurons of the NTS in a CCK1 receptor-dependent manner. Moreover, while the anorexigenic effect of palm-PrRP31 was not affected by JMV236, it was partially attenuated by devazepide in fasted mice. The present findings indicate that the exogenously influenced CCK system may be involved in the central anorexigenic effect of peripherally applied palm-PrRP31, which possibly indicates some interaction between the CCK and PrRP neuronal systems.
Keywords: stravovací zvyklosti; Male; Solitary Nucleus; přijímání potravy; anorektika; signální transdukce; chemokiny CC; mužské pohlaví; Hormone Antagonists; Eating; devazepid; sinkalid; Sincalide; Signal Transduction; Prolactin-Releasing Hormone; antagonisté hormonů; peptidové fragmenty; cholecystokinin; Paraventricular Hypothalamic Nucleus; Animals; nucleus paraventricularis hypothalami; omezení příjmu potravy; Cholecystokinin; injekce intraperitoneální; Injections, Intraperitoneal; zvířata; Fasting; Devazepide; myši inbrední C57BL; myši; nucleus solitarius; hormon uvolňující prolaktin; Mice, Inbred C57BL; protoonkogenní proteiny c-fos; Peptide Fragments; Chemokines, CC; Mice; Injections, Subcutaneous; Appetite Depressants; Proto-Oncogene Proteins c-fos; injekce subkutánní; Feeding Behavior